Parameter Estimation Of Wiener-Hammerstein Models - Shabaik, Emara (2020)
Several algorithms, namely the Output Error (OE), the Equation Error (EE), the Prediction Error (PE), and the Instrumental Variable (IV), for parameter estimation of Wiener-Hammerstein models, are derived. Monte Carlo simulation results are provided showing the effectiveness, and comparing the performance of these algorithms